Psychological Analysis of Forough Farrokhzad Poems Based on A. Adler and K. Horney Theories - Kolsoom Fazeli, Seyedeh (2020)
The objective of this study was to psychological analysis of Forough Farrokhzad poems based on A. Adler and K. Horney theories. This research has been done using descriptive method and content analysis in which researchers’ study Forough Farrokhzad works. Results show that Forough Farrokhzad has always been encountered with censorship and people's pessimism in our society that our traditional culture could not put up with her freedom that reflect her emotion, thoughts, and affections in her poems. These poems reflected both the difficulties she’s been through and also echo her psychological problems including inferiority, submission, aggression, and dissociative disorder. Indeed, her self-disclosure, supremacy, and self-chosen solitude were intentional attempted to cover and healed her weaknesses. After analyzing about Forough, we identified that her negative attitude to world and pessimism has created paranoia in some of her poetry. She was a pessimist in some of her poems and saw all the men and sometimes all the people as her enemy.